Students’ Difficulties in Listening Sessions through Liveworksheets At SMP Puri Artha Karawang - Nasywarindi, Meisya Afiyah; Arianti, Theresia (Foremost Journal, 2025)
Many students do not have a sufficient level of listening skill. Students’ difficulties in listening include the areas of pronunciation, stress, intonation, vocabulary, and syntactic structure. This study aimed to investigate listening sessions through LiveWorksheets at SMP Puri Artha Karawang. This study included 25 students from grade seven. In conducting the study, the researcher applied a descriptive qualitative method. The researcher used semi-structured interview questions as the instrument of this research. The findings show that students faced listening difficulties mostly because of different speaker accents. Mostly, the students used entertaining media to overcome this challenge. Moreover, it is also found that out of nine difficulties found, seven are related to listening in general and two are related specifically to the use of LiveWorksheets which are unclear audio/sounds and technical error.